Acceptability of Edible Food Packaging in Slovakia: A Case Study on Young Generation - Horská, Elena; Šedík, Peter; Mušinská, Kristína; Savitskaya, Tatsiana; Grinshpan, Dmitrij; Kačániová, Miroslava (Frontiers in Sustainable Food Systems, 2021)
The increasing problem of plastic pollution from food packaging created a new market potential for inventing environmental-friendly packaging in the food market including edible food packaging. The main objective of the study was to identify attitudes and perceptions of young people toward edible food packaging. Primary research was conducted via a questionnaire survey. The research sample involved 22 respondents between 19 and 30 years from Slovakia. A questionnaire survey was interconnected with sensory analysis where respondents tested 23 samples of edible food packaging. The results showed that consumers perceive as the most important aspect of food packaging the possibilities of their recycling, followed by the protective function and ecological aspect, while the least important aspect was the design of the packaging. The best rating based on the taste was obtained by sample no. 22 (Mentha × Piperita) while the worst rating was obtained by sample no. 3 (Zingiber officinale). The majority of tested edible food packaging had an indifferent taste.